Animal Model of Depression and Anxiety- PROS and CONS - Kaur, Ravinder; Rani, Ritu; Singh , Ajeet Pal; Singh, Amar Pal (Journal of Biomedical and Pharmaceutical Research, 2024)
The benefits as well as the drawbacks of using animal models to investigate depression and anxiety are discussed in this abstract. One of the main causes of the global illness burden is major depression. The primary causes of this condition are the disorder's chronicity, recurrence, and inadequate response to antidepressant treatment. Reliable animal models are necessary for this field to advance. The current models either rely on controlling the environment that rodents are exposed to.These changes have the potential to affect particular biological and behavioral outcomes that are linked to various pathophysiological and symptomatic aspects of major depression.Severe mental illness such as depression has an impact on world health. Its molecular mechanisms are investigated using a variety of animal models. Still, no plausible model is able to mimic the pathogenic mechanism. This review contrasts the benefits and drawbacks of prominent.Keywords: Depression; animal model; behaviour test, anxiety